Home care models dedicated to COVID-19 patients: the experience of a Local Health District of Veneto Region (Italy) - Manea, Silvia; Pinato, Marco; Salmaso, Laura; Vittorii, Silvia; Biasio, Michela; Rigoni, Matteo; Manfrin, Vinicio; Bertocco, Elisabetta; Zanatta, Mirko; Saia, Mario (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. During COVID-19 pandemic, health professionals have been working in an extreme uncertainty context. Affected patients needed to be cared at home as long as possible to avoid virus spreading and hospital resources saturation. The Veneto Regional Administration (North-east of Italy) released Regional guidelines about it. The Western Healthcare District of the Local Health Authority of the city of Vicenza (180,000 inhabitants) implemented a healthcare pathway following them. Aim of the study is to describe the results and outcomes of such implementation. Methods. In the implemented health care pathway, a new service called “Special Unit of continuity of care” (USCA) with physicians and nurses has been dedicated to the prise en charge at home of patients suffering from Sars-CoV-2. They were referred to the USCA by general practitioners or by hospital specialists, and managed through a daily clinical monitoring by regular home visits and phone calls, specialist consultations and therapy management. In order to prevent hospital admission, an oxygen concentrator when possible has been employed and managed at home by the members of the USCA when the oxygen saturation was below 93%. An observational retrospective study has been conducted using anonymized data from different databases: the USCA activity database (from 12/01/20 to 21/31/21), the hospital and Emergency Department discharge databases, and the “healthcare co-payments exemptions database”. The latter database refers to the people excluded - because of their chronicity - from the co-payment of a list of medical exams and services. Descriptive and multivariate logistic regression analyses have been implemented. Results. 1,419 patients suffering from Sars-CoV-2 have been cared and managed by the USCA in the considered period of time (mean 11.4 days), of whom 787 (55.5%) with at least one chronic condition (described in the above quoted “healthcare co-payments exemption database”) and 261 provided with oxygen concentrator. 275 (19.4%) needed a hospital admission, 39 (2.8%) in intensive unit; 53 died during hospitalization (3.8%). Out of the 261 patients utilizing oxygen concentrator, 103 have been admitted to hospital (39.5%), 7.3% in intensive unit and 8.0% died. In implemented multivariate analyses, the use of oxygen concentrator, proxy measure of the severity of the condition, is the major determinant for the risk of hospital admission (adj OR: 3.2, CI 2.3-4.3) and of dying within 30 days (adj OR: 2.8 CI 1.5-5.1). Among the 261 patients provided with oxygen concentrator, 158 (60,5%) have been managed at home without any admission to emergency department and/or hospitalization. Conclusions. In an uncertain context such as COVID-19 pandemic, the already-implemented home care model has been modified by integrating the USCA physicians and nurses and specialist care networks to prevent hospitalization and the sense of isolation and abandonment of people as much as possible. Almost 1,500 patients suffering from COVID-19 have been cared for at home over 13 months by such new service with complex and multidisciplinary activities. The risk of hospitalization and death appears determined by the severity of the pathology with high and significant OR 60% of patients with oxygen concentrators who, despite an initial high hyposaturation were not hospitalized, represent, partly, the group of patients who would have been requiring hospital care in the absence of a home care pathway in a standard situation.